Understanding sprint velocity fluctuations for improved project plans with Scrum: a case study. Issue 9 (2nd August 2014) - Albero Pomar, Filipe; Calvo‐Manzano, Jose A.; Caballero, Edgar; Arcilla‐Cobián, Magdalena; Biró, M.; Messnarz, R.; Colomo‐Palacios, R.
ABSTRACT Starting from the documentation of high sprint velocity fluctuations in a Scrum project, this paper presents a thorough approach to identify the sources of issues arising in the context of Scrum implementation. Given that Scrum provides guidance on identifying process issues but not their root causes, various approaches are explored. This is of great relevance because Scrum defines project schedules relying heavily on sprint velocity and because it is the most widely used agile methodology. The findings provide a new approach to evaluate such fluctuations and establish a more realistic project assessment than what is currently defined by Scrum. In this respect, this paper contributes to improve the understanding of the software development process using this agile framework. Copyright © 2014 John Wiley & Sons, Ltd.